2015
DOI: 10.4187/respcare.04066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inspiratory Time and Lung Compliance on Flow Bias Generated During Manual Hyperinflation: A Bench Study

Abstract: BACKGROUND: Manual hyperinflation can be used to assist mucus clearance in intubated patients. The technique's effectiveness to move mucus is underpinned by its ability to generate flow bias in the direction of expiration, and this must exceed specific thresholds. It is unclear whether the inspiratory times commonly used by physiotherapists generate sufficient expiratory flow bias based on previously published thresholds and whether factors such as lung compliance affect this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moreover, the shorter V T delivered in this study (mean of 643 mL) might explain why a T INSP shorter than two seconds (mean of 1.84 s) was able to generate an adequate expiratory flow bias. A recent bench study demonstrated that, to achieve sufficient expiratory flow bias during MH, it was necessary to have a T INSP of at least three seconds with normal compliance lungs and two seconds with lower compliance lungs [ 31 ]. However, in their study the delivered V T was standardized in 1.4 L which, clearly, required a longer T INSP to generate a lower PIF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the shorter V T delivered in this study (mean of 643 mL) might explain why a T INSP shorter than two seconds (mean of 1.84 s) was able to generate an adequate expiratory flow bias. A recent bench study demonstrated that, to achieve sufficient expiratory flow bias during MH, it was necessary to have a T INSP of at least three seconds with normal compliance lungs and two seconds with lower compliance lungs [ 31 ]. However, in their study the delivered V T was standardized in 1.4 L which, clearly, required a longer T INSP to generate a lower PIF.…”
Section: Discussionmentioning
confidence: 99%
“…8 cmH2O) to reduce excess pressure being applied, increasing sleep efficiency while preventing overdistension of the lung tissue. APAP devices are the most complex, with automatic PEEP adjustments performed on a breath-by-breath basis from additional inline and auditory sensor measurements to detect periods without breathing [18] . Adjustments between clinician-set boundaries of 4–20 cmH2O are performed through algorithms based on the detection of inspiratory flow limitation, snoring, apnea events, and obstructive pressure in device sensor measurements [12] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…A Michigan Instruments Training and Testing Mechanical Lung (Michigan, USA) was used to validate the mePAP with ‘breaths’ of known and controlled compliance and tidal volume. The lung was set to a compliance of 0.05 L/cmH2O to simulate a normal adult’s lung [18] .…”
Section: Validation and Characterisationmentioning
confidence: 99%
“…The studies conducted in the United Kingdom have reported that 32% of the physiothearpists used MHI without a manometer and 41% with a manometer [ 17 ]. An Australian study reported that 31% of physiotherapists used a manometer and 51% set PIP < 40cmH 2 O [ 18 ]. This study further reported that a high PEFR is obtained by the slow squeeze during inspiration and quick release during expiration in manual hyperinflation.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%